Characterization of ultrafast free‐electron laser pulses using extreme‐ultraviolet transient gratings. (18th December 2017) - Capotondi, F.; Foglia, L.; Kiskinova, M.; Masciovecchio, C.; Mincigrucci, R.; Naumenko, D.; Pedersoli, E.; Simoncig, A.; Bencivenga, F.
Abstract : The advent of ultra‐short extreme ultraviolet (EUV) and soft X‐ray free‐electron laser (FEL) sources able to produce high peak brightness and sub‐picosecond pulses requires novel time‐domain diagnostics to provide temporal information on the emitted pulse duration. Here the successful implementation of an autocorrelation method to determine the FEL–FEL pulse duration based on an EUV transient grating is reported. Abstract : The characterization of the time structure of ultrafast photon pulses in the extreme‐ultraviolet (EUV) and soft X‐ray spectral ranges is of high relevance for a number of scientific applications and photon diagnostics. Such measurements can be performed following different strategies and often require large setups and rather high pulse energies. Here, high‐quality measurements carried out by exploiting the transient grating process, i.e. a third‐order non‐linear process sensitive to the time‐overlap between two crossed EUV pulses, is reported. From such measurements it is possible to obtain information on both the second‐order intensity autocorrelation function and on the coherence length of the pulses. It was found that the pulse energy density needed to carry out such measurements on solid state samples can be as low as a few mJ cm −2 . Furthermore, the possibility to control the arrival time of the crossed pulses independently might permit the development of a number of coherent spectroscopies in the EUV and soft X‐ray regime, such as, for example, photon echo and two‐dimensional spectroscopy.